Use of tongue twisters to enhance pronunciation in EFL high school seniors. - Campoverde-Llivisaca, Erika Valeria (My University, 2021)
The aim of this work is to enhance students’ pronunciation skills through the use of various activities based on tongue twisters. Tongue twisters are not used as much in the teaching of a second language; however, this tool shows greats benefits when used in the class specifically for the speaking and pronunciation skills. Educators can teach a specific sound to enhance students’ pronunciation through the use of a tongue twisters making the class completely change from a traditional one into a more creative and innovative class. Additionally, tongue twisters are considered to have an impact on motivation and they are a great tool to develop students’ phonemic awareness that is usually left behind or never taught in class. Through the use the tongue twisters, students develop that awareness and practice certain sounds that are not part of their repertoire, and by working with them, learners could achieve that phonemic awareness. As a result, these lesson plans help students to improve their overall pronunciation abilities.
Keywords: tongue twisters; speaking; pronunciation; phonemes; sounds; Máster Universitario en Enseñanza de Inglés como Lengua Extranjera